Implementation of The Kid’s Athletics Program on Gross Motor Skills and Sportsmanship of Elementary School Students - Jaka Hasbi Fabian; Ricky Wibowo; Eva Sri Gumilang (Journal of Physical Education Health and Sport, 2025)
This study aims to examine the effect of the Kids Athletics program implementation on the gross motor skills and sportsmanship attitudes of elementary school students. The research method used was a quasi-experiment with a pretest-posttest design. The research subjects consisted of 64 elementary school students. The instruments used were the Test of Fundamental Motor Skills (FUS) and the validated YSVQ-2 Questionnaire. Data analysis was conducted to determine significant changes before and after program implementation. The results showed an increase in FUS of approximately 3.125% in the control group and 75% in the experimental group, while the YSVQ-2 showed similar but different results, namely an increase of 6.25% in the control group and 62.5% in the experimental group. It can be concluded that the implementation of the kids athletics program is effective in improving the gross motor skills and sportsmanship of elementary school students. Based on the findings of this alternative study, it is recommended that the kids athletics program be implemented as a Physical Education (PE) learning strategy to improve the basic motor skills and affective aspects of elementary school students.